2020
DOI: 10.3390/ijms21062235
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticancer Evaluation and Structure-Activity Analysis of Novel (E)- 5-(2-Arylvinyl)-1,3,4-oxadiazol-2-yl)benzenesulfonamides

Abstract: To learn more about the structure–activity relationships of (E)-3-(5-styryl-1,3,4-oxadiazol-2-yl)benzenesulfonamide derivatives, which in our previous research displayed promising in vitro anticancer activity, we have synthesized a group of novel (E)-5-[(5-(2-arylvinyl)-1,3,4-oxadiazol-2-yl)]-4-chloro-2-R1-benzenesulfonamides 7–36 as well as (E)-4-[5-styryl1,3,4-oxadiazol-2-yl]benzenesulfonamides 47–50 and (E)-2-(2,4-dichlorophenyl)-5-(2-arylvinyl)-1,3,4-oxadiazols 51–55. All target derivatives were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…The last one seems to be the most detailed, and it is precisely this that we will try to implement in the course of our narrative. As it should be expected, a priori, most of the publications in this direction are devoted to organic compounds, and primarily organic molecules; these include, with varying degrees of correctness, publications [ 1 , 2 , 3 , 102 , 103 , 104 , 106 , 108 , 112 , 117 , 118 , 119 , 121 , 124 , 127 , 128 , 130 , 131 , 132 , 133 , 135 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 146 , 147 , 148 , 151 , 153 , 154 , 156 , 157 , 164 , 165 , 166 , 168 , 171 , 172 , 174 , 176 , 178 , 180 , 183 , 185 , 186 ]. Much less space is occupied by the works related to polymeric (in fact, to a high molecular weight) compounds [ 113 , …”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…9 1,3,4-Oxadiazole and its derivatives have great biological properties 10 with many examples in the literature such as antiviral, antifungal, antimicrobial, anti-inflammatory and anticancer activities. [11][12][13][14][15] Moreover, many studies showed that the existence of more than two heterocyclic units may lead to an increase the antimicrobial activity significantly. 16 Schiff bases are compounds carrying azomethine functional group 17 (C=N), Schiff bases obtained from complexes derived heterocycles have a great importance in the field of pharmaceutical industries due to versatile uses in synthetic intermediates and the wide range of biological properties.…”
Section: Introductionmentioning
confidence: 99%